Biofilm Structures in a Mono-Associated Mouse Model of Clostridium difficile Infection - Soavelomandroso, Anna P.; Gaudin, Françoise; Hoys, Sandra; Nicolas, Valérie; Vedantam, Gayatri; Janoir, Claire; Bouttier, Sylvie (Frontiers in Microbiology, 2017)
Clostridium difficile infection (CDI) is a major healthcare-associated disease with high recurrence rates. Host colonization is critical for the infectious process, both in first episodes and in recurrent disease, with biofilm formation playing a key role. The ability of C. difficile to form a biofilm on abiotic surfaces is established, but has not yet been confirmed in the intestinal tract. Here, four different isolates of C. difficile, which are in vitro biofilm producers, were studied for their ability to colonize germ-free mice. The level of colonization achieved was similar for all isolates in the different parts of the murine gastrointestinal tract, but pathogen burden was higher in the cecum and colon. Confocal laser scanning microscopy revealed that C. difficile bacteria were distributed heterogeneously over the intestinal tissue, without contact with epithelial cells. The R20291 strain, which belongs to the Ribotype 027 lineage, displayed a unique behavior compared to the other strains by forming numerous aggregates. By immunochemistry analyses, we showed that bacteria were localized inside and outside the mucus layer, irrespective of the strains tested. Most bacteria were entrapped in 3-D structures overlaying the mucus layer. For the R20291 strain, the cell-wall associated polysaccharide PS-II was detected in large amounts in the 3-D structure. As this component has been detected in the extrapolymeric matrix of in vitro C. difficile biofilms, our data suggest strongly that at least the R20291 strain is organized in the mono-associated mouse model in glycan-rich biofilm architecture, which sustainably maintains bacteria outside the mucus layer.